Developing core economic parameter sets for asthma studies: A realist review and an analytical framework - Roukas, Chris; Quayyum, Zahidul; Patel, Anita; Fitzsimmons, Deborah; Phillips, Ceri; Hounsome, Natalia (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2020-037889 The Journal's website is at: https://bmjopen.bmj.com/content/10/10/e037889